FORMULATION OF FINANCIAL STATEMENT OBJECTIVES AND THE CONCEPT OF ISLAMIC BUSINESS ENTITIES OF NON-FINANCIAL COMPANIES - Isgiyarta, Jaka (Riset Akuntansi Keuangan, 2024)
Accounting is a cultural product, so the concepts developed in accounting are never separated from the cultural values in which accounting grows and develops. Islam has values that are different from capitalist values. Islamic values in economic life known as the Hall Mark of Islamic Economics. The concept of the objective of financial statements and the concept of corporate entities are fundamental in the development of accounting. These two concepts form the basis for determining the material components of the company's financial statements. The formulation of the concept of the objectives of the financial statements and the concept of the accounting entity cannot be separated from the desired or prevailing social values of society. In Islamic values, the hall mark values of the Islamic economy become the basis for the formulation of the concept of the objective of financial statements and the concept of corporate entities.